Partial vs. superficial parotidectomy for surgical treatment of pleomorphic adenoma of the parotid gland: Primerjava rezultatov parcialne in superfacialne parotidektomije v zdravljenju pleomorfnega adenoma parotidne žleze - Čizmarevič, Bogdan; Lanišnik, Boštjan; Dinevski, Dejan (Acta Medico-Biotechnica, 2021)
Purpose: Superficial parotidectomy is still the gold standard in surgical therapy for pleomorphic adenoma. Recently, less extensive procedures such as extracapsular dissection and before that partial parotidectomy were introduced. We analyzed the data of patients treated with either partial or superficial parotidectomyand compared recurrence rates and postoperative morbidity.Methods: WA retrospective analysis of all the patients with pleomorphic adenomas who were treated at the Department of Otolaryngology from 2002 to 2016 was performed. The patients’ data were analyzed for outcome measures: facial nerve deficit, margin status, Frey’s syndrome, tumor size, duration of surgery and tumor recurrence.Results: During this period, 186 patients with pleomorphic adenomas of the parotid gland underwent surgery, 177 of these for the first time. Nine patients were referred to us with recurrence from another institution. Among these 177 patients, 86 were treated by partial parotidectomy, 75 by superficial parotidectomy and 16 by total parotidectomy. Transient facial weakness and the duration of surgery differed significantly between the different types of operation. Frey’s syndrome and recurrence rate were not significantly different between the groups.Conclusions: Radical surgery could be achieved with limited removal of the parotid while the recurrence rate was the same between the groups.
Keywords: partial parotidectomy; superficial parotidectomy; pleomorphic adenoma; Frey syndrome; recurrence; facial nerve lesion